Zakaj poučevati matematiko - Felda, Darjo; Cotič, Mara (Revija za elementarno izobraževanje, 2012)
Why teach mathematics. When first introducing mathematical contents to children as part of early mathematics instruction, we tend to refer to abstract notions rather than to the experience that children already have, by which we break the link between mathematics and the material world or at least between mathematics and the kind of mathematical world that children already know. Contrary to that, teachers should give pupils guidance to help them increase the level of their mathematical literacy in line with their experiences and abilities and at the same time build abstract mathematical reflection of the material world and to enrich their own mathematical language. Recently, the importance of play or those activities in which children are actively involved has been emphasised. Through personal identification with a problem situation and problem solving, a child is supposed to learn about new concepts and strategies. However, doubts have emerged as to whether this kind of instruction has really come to life in teaching practice or whether such activities have been introduced merely as an initial motivation which fades away into mere transmission or reception of factographic knowledge. Children must regularly adjust the newly acquired knowledge to the priorly mastered knowledge and link mathematics to real-time situations. This is the only way for them to feel safe, satisfied, and successful and to be motivated for attaining new knowledge, through which mathematics instruction gets a true meaning.